Developing Entrepreneur’s Ethics from the Principles of Tawhidic Paradigm: An Empirical Study in Malaysia - Salim, Farah Akmar Ano (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores the critical importance of Tawhidic paradigm in improvising current entrepreneurship training curriculum. It proposes general model that may be adapted by all institutes of higher learning in Malaysia (IHLs). This paper proposes basic components of the paradigm and illustrates the application of selected aspects of the components in the curriculum. The conceptual study discusses the major components of the Tawhidic paradigm and provides illustration that help link the spirit of Tawhid with the entrepreneur’s characteristics to nurture the humanistic skills, ethics and values. The characteristics should integrated with the ethos of Tawhid which harmonize other worldly (Al-Akhirah) (the Hereafter) and the worldly (Al- Duniya). With this spiritual awareness embedded into entrepreneur’s personal character, the objectives and mission in reinforcing values, which referred to as promotion of goodness (amr bil ma’aruf) and prevention of evil (nahi anil munkar) will achieve. The proposed framework makes continuous learning in promoting the entrepreneur’s training curriculum in the Malaysian context, specifically to the Muslim world in general. In addition, the survey revealed that inculcating Islamic principles and ethics in entrepreneur’s activities can increase their credibility in conducting business with others besides being resilient in developing the business (concept of taqwa)